The Concept of Dhikr in Sufism and Its Practices and Benefits in Life - Wiwi Dwi Daniyarti; Muhammad Thoriq; Ega Bagas Pradana; Safira Dwi Nurida (Journal Analytica Islamica, 2023)
This journal examines the concept of dhikr in Sufism, which is a branch of spirituality in the Islamic religion. Dhikr literally means remembering or chanting the name of Allah. In Sufism, dhikr has a central role as a tool to get closer to Allah, achieve spiritual awareness, and achieve the ultimate human goal of achieving a higher existence. This journal explores dhikr practices commonly carried out in Sufism, such as dhikr jahr (dhikr done aloud), dhikr khafi (dhikr done silently), and dhikr halqi (dhikr done with breathing movements). This dhikr practice is carried out regularly and repeatedly, with the aim of eliminating mental distractions and focusing on the presence of Allah. Apart from that, this journal also highlights the benefits of dhikr in everyday life. The practice of dhikr is known to have a positive effect on an individual's mental and spiritual well-being. Dhikr can help reduce stress, increase concentration, strengthen your relationship with God, and deepen your understanding of the meaning of life. Dhikr is also considered a means of cleansing the heart of negative traits, such as arrogance, envy, and malice, as well as developing positive traits, such as patience, compassion, and sincerity. This journal uses qualitative research methods by reviewing literature and primary sources in the field of Sufism and Islamic spirituality. The results of this research provide a better understanding of the concept of dhikr in Sufism, related practices, and its benefits in everyday life.Jurnal ini mengkaji konsep dzikir dalam tasawuf, yang merupakan cabang spiritualitas dalam agama Islam. Dzikir secara harfiah berarti mengingat atau menyebut nama Allah. Dalam tasawuf, dzikir memiliki peran sentral sebagai alat untuk mendekatkan diri kepada Allah, mencapai kesadaran spiritual, dan mencapai tujuan akhir manusia untuk mencapai keberadaan yang lebih tinggi. Jurnal ini mengeksplorasi praktik dzikir yang umum dilakukan dalam tasawuf, seperti dzikir jahr (dzikir yang dilakukan dengan lantang), dzikir khafi (dzikir yang dilakukan dalam hati), dan dzikir halqi (dzikir yang dilakukan dengan gerakan pernafasan). Praktik dzikir ini dilakukan secara rutin dan berulang-ulang, dengan tujuan menghilangkan gangguan pikiran dan fokus pada kehadiran Allah. Selain itu, jurnal ini juga menyoroti Manfaat dzikir dalam kehidupan sehari-hari. Praktik dzikir diketahui memiliki efek positif pada kesejahteraan mental dan spiritual individu. Dzikir dapat membantu mengurangi stres, meningkatkan konsentrasi, menguatkan hubungan dengan Tuhan, dan memperdalam pemahaman akan makna kehidupan. Dzikir juga dianggap sebagai sarana untuk membersihkan hati dari sifat-sifat negatif, seperti kesombongan, iri hati, dan kedengkian, serta mengembangkan sifat-sifat positif, seperti kesabaran, kasih sayang, dan ketulusan. Jurnal ini menggunakan metode penelitian kualitatif dengan mengkaji literatur dan sumber-sumber primer dalam bidang tasawuf dan spiritualitas Islam. Hasil penelitian ini memberikan pemahaman yang lebih baik tentang konsep dzikir dalam tasawuf, praktik-praktik yang terkait, dan manfaatnya dalam kehidupan sehari-hari.